2022
DOI: 10.1002/trtr.2130
|View full text |Cite
|
Sign up to set email alerts
|

Building Critical Reading and Critical Literacy With Picturebook Analysis

Abstract: MORE TO EXPLORE■ Check out blogs to get recommendations for literature that reflects diverse perspectives. These are excellent starting places: American Indians in Children's Literature, The Brown Bookshelf, Hijabi Librarians, and Latinxs in Kid's Lit.■ Hudson, A. K. ( 2016). Get them talking! Using student-led book talks in the primary grades. The Reading Teacher, 70(2), 221-225.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Critical literacy places the text within political, historical, and social context while challenging issues of equity (Cervetti et al., 2001). Selected texts can critically engage students and provide access to challenging issues (Wells et al., 2022). Discussion around this book can relate to foods that students might reject and why their families continue to force them even though they have showed disdain for them.…”
Section: Overview Of Three Lenses Frameworkmentioning
confidence: 99%
“…Critical literacy places the text within political, historical, and social context while challenging issues of equity (Cervetti et al., 2001). Selected texts can critically engage students and provide access to challenging issues (Wells et al., 2022). Discussion around this book can relate to foods that students might reject and why their families continue to force them even though they have showed disdain for them.…”
Section: Overview Of Three Lenses Frameworkmentioning
confidence: 99%
“…The field has attempted to make strides in correcting this injustice through engagement with culturally relevant, responsive and sustaining pedagogical methods, as well as CIL methods. Regarding CIL in particular, some scholars view the method as a means to democratize information and participation in society (Powell et al, 2001) while others see CIL as a means to develop political agency (Smith, 2013), but questions remain: whose democracy is being described? What type of political agency is being described?…”
mentioning
confidence: 99%
“…Backmatter, and other peritext, included in picture books allows them to be used to teach information literacy (Cappiello & Hadjioannou, 2022); author notes allow for investigations of positionality (Kaczmarczyk & Adams, 2021) and craft. Additionally, picture books are used to teach critical reading and critical literacy skills (Wells et al, 2022). Picture books can, when investigated through critical literacy frameworks support readers' developing racial literacies (Husband, 2018).…”
Section: Picture Books As Multipurpose Teaching Toolsmentioning
confidence: 99%
“…Picture books are also accessible in schools, as reflected in a review of extant literature which found an abundance of research on using picture books through elementary school (Ciecierski et al, 2017;Cappiello & Hadjioannou, 2022;Lysaker & Sedberry, 2015;Lysaker & Tonge, 2013;Morgan et al, 2021, Wells et al 2022. It is interesting that the research on the use of picture books in schools appears to dwindle as students age.…”
Section: Racial Identity and Racial Literacy Developmentmentioning
confidence: 99%